Influence of mothers’ and frontline health workers’ knowledge, attitude, and practices on infant and young child feeding and child nutrition: a cross-sectional study in aspirational districts of Assam, India - Randhawa, Sonali; Choudhury, Manisha; Choudhary, Devika Gali; Ballala, Ramnath; Hegde, Shailendra; Barman, Priyanka; Dogra, Vishal (Frontiers in Nutrition, 2024)
The knowledge, attitude, and practices (KAP) of mothers and frontline health workers (FLWs) regarding optimal Infant and Young Child Feeding (IYCF) are essential for mitigating undernutrition and associated morbidities among under-five children. The study assessed the KAP of mothers (of children aged 0–60 months) and FLWs regarding recommended IYCF practices, the association of mother’s KAP with their demographic characteristics and children’s nutritional outcomes, and the prevalence of stunting, wasting, and underweight among children aged 0–60 months in five high-focus districts of Assam. Data were collected from 389 mothers, 456 children, and 138 FLWs using a standard method. Of the 389 mothers, 29% had good KAP scores, 42% scored average, and 29% had poor KAP scores regarding IYCF practices. The mean KAP score increased significantly with improvements in variables such as community, language, education level, monthly income, and living conditions (p < 0.01). Less than half of the children were stunted (40%), one-third were affected by wasting (28%), and approximately 43% were underweight. Children whose mothers had a KAP score of less than 40% were 2.05 times more likely to experience stunting (CI = 1.04–4.02) than those whose mothers scored above 60%. Similar findings were reported for wasting and underweight. Of the 138 FLWs, 56% had good KAP scores, 30% had average scores, and 14% had poor scores. There was a noticeable gap in the KAP of the mothers regarding IYCF practices compared to that of FLWs. A comprehensive intervention plan to improve feeding practices can enhance the nutritional status of under-five children.